Buried bumper syndrome – a rare complication of percutaneous endoscopic gastrostomy tube feeding - Borkowska, Anna; Jankowska, Agnieszka; Szlagatys-Sidorkiewicz, Agnieszka; Landowski, Piotr; Kamińska, Barbara (Gastroenterology Review/Przegląd Gastroenterologiczny, 2012)
Percutaneous endoscopic gastrostomy is one of the most prevalent methods of alimentation when oral feeding is not possible. The insertion procedure, maintenance and tending of gastrostomy are relatively safe. However, some complications occur. One of them is buried bumper syndrome. This is embedding of the internal bolster of the gastrostomy tube in the gastric mucosa. In this paper we present a case of a 3-year-old boy with buried bumper syndrome.